IL-15 gene mutation as a molecular risk factor in acute lymphoid leukemia: Interleukin-15 gene mutation in ALL - Mohammed, Sarbaz Ibrahim; Hassan, Kawa Muhamed-amin; Azeez, Darya Mohammed; Qadir, Fikry Ali; Salihi, Abbas Burhan (Cellular and Molecular Biology, 2024)
The present study investigated the relationship between single nucleotide polymorphisms in the interleukin (IL)-15 gene located (exon 8) on the chromosomal location 4q31.21 and acute lymphoblastic leukaemia (ALL) risk in Iraqi patients. A total of 78 (49 male -29 female) primary ALL (62B-cell, 16 T-cells lineages cases and 30 healthy control subjects (median age 11, age range were 4-21.5), were enrolled at the Nanakaly Hospital of Erbil Province between February 2021 and January 2022. The genotype analysis was performed using polymerase chain reaction (PCR) and Sanger DNA sequencing. The IL15 homozygous rs10833 (100%) and rs2291596 (63.6%) genotypes indicated high frequencies and were associated with a risk of developing ALL, while the remaining 16 novel mutations indicated in low frequency (9.1%) except for the 97270G>GT genotype (18.2%). High expression levels were noted for different clusters of differentiation (CD) biomarkers between both subtypes of ALL, including, CD10, CD19, CD22, CD79a, CD99, terminal deoxynucleotidyl transferase (TdT), and human leukocyte antigen DR (HLA-DR) isotype in B-cells lineages, while, CD2, CD3, CD5, CD7, CD13, CD117 and TdT are more specific to T-cells lineages. On the other hand, significant changes were noted in certain hematological parameters including red blood cells (RBCs), haemoglobin (g/dl), haematocrite (HCt %), red blood cell distribution width (RDW %), and platelet counts (PLT- 109/L) compared with those of healthy subjects. Finally, it was concluded that various novel mutations were recorded with different subtypes of ALL diseases, and mild anemia was observed among patients. Future studies will be towered to associate these mutations with prognosis and therapeutic response of diseases.